2005
DOI: 10.1074/jbc.m501052200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Active Site Residues of the Fosfomycin Resistance Enzyme FosA from Pseudomonas aeruginosa

Abstract: The metalloglutathione transferase FosA catalyzes the conjugation of glutathione to carbon-1 of the antibiotic fosfomycin, rendering it ineffective as an antibacterial drug. Codon randomization and selection for the ability of resulting clones to confer fosfomycin resistance to Escherichia coli were used to identify residues critical for FosA function. Of the 24 codons chosen for randomization, 16 were found to be essential because only the wild type amino acid was selected. These included ligands to the Mn 2؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 35 publications
3
35
1
2
Order By: Relevance
“…The consumption of GSH catalyzed by FosA3 and FosC2 was confirmed using Ellman's reagent. These results indicated that FosA3 and FosC2 inactivated fosfomycin by exerting GSH S-transferase activity, very similar to FosA TN and FosA PA (1,3). In conclusion, we report here the prevalence of fosfomycin resistance among CTX-M-producing E. coli isolates in Japan, together with the emergence of two novel plasmid-borne fosfomycin-modifying enzymes, FosA3 and FosC2.…”
mentioning
confidence: 70%
“…The consumption of GSH catalyzed by FosA3 and FosC2 was confirmed using Ellman's reagent. These results indicated that FosA3 and FosC2 inactivated fosfomycin by exerting GSH S-transferase activity, very similar to FosA TN and FosA PA (1,3). In conclusion, we report here the prevalence of fosfomycin resistance among CTX-M-producing E. coli isolates in Japan, together with the emergence of two novel plasmid-borne fosfomycin-modifying enzymes, FosA3 and FosC2.…”
mentioning
confidence: 70%
“…Fosfomycin resistance was first reported in the early 1980s in a clinical Serratia marcescens strain carrying a plasmid-mediated transposable element, Tn2921, which harbored the fosA gene flanked by two terminal copies of an identical insertion sequence (8). The fosA gene product is a glutathione S-transferase, a metalloenzyme transferred through plasmids to Enterobacteriaceae, with two other variants found in Pseudomonas aeruginosa (9). New subtypes of fosA with similar structures have been described (fosA2, fosA3, fosA4, fosA5 fosA6, fosB, fosC, fosC2, fosX, and fosK); the mechanism of resistance associated with each of them has been reviewed elsewhere (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…To elucidate whether the persistence phenotype is associated with this enzymic activity, we performed the persistence assay on PAO1 overexpressing the mutant fosA R119A allele. In this allele, Arg 119 is replaced by Ala 119 and prevents the gene product from conferring resistance to fosfomycin in E. coli (Beharry & Palzkill, 2005). Arg 119 is located in the active site of FosA and is assumed to be involved in direct binding of the substrate (Bernat et al, 1999;Smoukov et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type fosA + (PA1129) was PCR-amplified with Pfx polymerase (Invitrogen) using isolated genomic DNA of P. aeruginosa PA14 as template. The mutant fosA R119A allele was amplified using pTP123 (kindly provided by Timothy Palzkill, Baylor College of Medicine, TX, USA) as a template (Beharry & Palzkill, 2005). PCR amplifications were performed using primers SPI-1559 and SPI-1713 (Table 2).…”
mentioning
confidence: 99%